2021
DOI: 10.1093/jac/dkab321
|View full text |Cite
|
Sign up to set email alerts
|

Impact of remdesivir according to the pre-admission symptom duration in patients with COVID-19

Abstract: Background The use of remdesivir has demonstrated a significant reduction in the time to recovery in patients with COVID-19. However, the impact on mortality is still controversial. Therefore, it is necessary to evaluate whether there is a specific subgroup of patients in whom an active antiviral therapy also reduces the mortality. Methods Patients admitted for >48 h in our hospital for a SARS-CoV-2 confirmed or suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…Identifying patients with rapidly developing pneumonia and a high risk of developing acute respiratory distress syndrome (ARDS) as soon as possible might help individualize pharmacological treatment and optimal utilization of medical resources. It was demonstrated that the sooner pharmacological treatment is started in such patients, the greater are the chances of survival [ 15 , 16 , 17 , 18 ]. We found that patients with more extensive lung changes on admission objectified by a higher TSS were likely to present with fever, had decreased finger oxygen saturation and arterial oxygen partial pressure, increased laboratory indicators of inflammation including serum c-reactive protein and ferritin, and decreased lymphocytes count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying patients with rapidly developing pneumonia and a high risk of developing acute respiratory distress syndrome (ARDS) as soon as possible might help individualize pharmacological treatment and optimal utilization of medical resources. It was demonstrated that the sooner pharmacological treatment is started in such patients, the greater are the chances of survival [ 15 , 16 , 17 , 18 ]. We found that patients with more extensive lung changes on admission objectified by a higher TSS were likely to present with fever, had decreased finger oxygen saturation and arterial oxygen partial pressure, increased laboratory indicators of inflammation including serum c-reactive protein and ferritin, and decreased lymphocytes count.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HD patients are characterized by impaired innate immunity and a worse humoral and cellular response to vaccines than in the general population [ 12 , 13 , 14 ]. Various methods of pharmacological treatment, including inhaled steroids, casirivimab-imdevimab, remdesivir, and tocilizumab are highly hoped for, which, as research shows, if applied early enough, can significantly improve the prognosis [ 15 , 16 , 17 , 18 ]. Therefore, the need to identify patients infected with SARS-CoV-2 and those who develop pneumonia, which may be fatal or have persistent sequelae, remains as urgent as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Data were retrospectively collected for all patients included in the study from the electronic health records (EHRs). An intelligent system was used to retrieve the high-quality data from EHRs (SILDv1.0 system, S34M @ ) as previously described [ 8 ]. Variables included were: age, gender, pre-admission duration of symptoms in days, co-morbidities (hypertension, chronic heart disease, diabetes mellitus, chronic liver disease, chronic kidney disease, chronic obstructive pulmonary disease, haematological and solid neoplasia), respiratory rate and ambient air arterial oxygen saturation (SaO 2 ) measured with a pulse oximeter at admission, creatinine, lymphocyte count, C-reactive protein (C-RP), lactate dehydrogenase (LDH), d -dimer, ferritin and procalcitonin within the first 24 h from hospital admission.…”
Section: Methodsmentioning
confidence: 99%
“…We looked for controls born in Spain with the same age and gender among the 3216 patients recorded in our previously described database [ 8 ]. No other variables were used for matching patients.…”
Section: Methodsmentioning
confidence: 99%
“…In an observational study carried out in Spain at the Hospital Clínico de Barcelona, the use of remdesivir improved survival, with greater efficacy in patients who received treatment earlier, with a total reduction in the risk of death of 62% [ 16 ]. Other studies showed similar results, such that treated patients had less need for mechanical ventilation and lower mortality [ 17 , 18 ].…”
Section: Some Clinically Effective Antivirals Against Covid-19mentioning
confidence: 99%